Interlaboratory comparison investigations (ICIs) and external quality assurance schemes (EQUASs) for flame retardant analysis in biological matrices: Results from the HBM4EU project - Dvorakova, Darina; Pulkrabova, Jana; Gramblicka, Tomas; Polachova, Andrea; Buresova, Martina; López, Marta Esteban; Castaño, Argelia; Nübler, Stefanie; Haji-Abbas-Zarrabi, Karin; Klausner, Nadine; Göen, Thomas; Mol, Hans; et al. (Environmental Research, 2021)
The European Human Biomonitoring Initiative (HBM4EU) is coordinating and advancing human biomonitoring (HBM). For this purpose, a network of laboratories delivering reliable analytical data on human exposure is fundamental. The analytical comparability and accuracy of laboratories analysing flame retardants (FRs) in serum and urine were investigated by a quality assurance/quality control (QA/QC) scheme comprising interlaboratory comparison investigations (ICIs) and external quality assurance schemes (EQUASs). This paper presents the evaluation process and discusses the results of four ICI/EQUAS rounds performed from 2018 to 2020 for the determination of ten halogenated flame retardants (HFRs) represented by three congeners of polybrominated diphenyl ethers (BDE-47, BDE-153 and BDE-209), two isomers of hexabromocyclododecane (α-HBCD and γ-HBCD), two dechloranes (anti-DP and syn-DP), tetrabromobisphenol A (TBBPA), decabromodiphenylethane (DBDPE), and 2,4,6-tribromophenol (2,4,6-TBP) in serum, and four metabolites of organophosphorus flame retardants (OPFRs) in urine, at two concentration levels. The number of satisfactory results reported by laboratories increased during the four rounds. In the case of HFRs, the scope of the participating laboratories varied substantially (from two to ten) and in most cases did not cover the entire target spectrum of chemicals. The highest participation rate was reached for BDE-47 and BDE-153. The majority of participants achieved more than 70% satisfactory results for these two compounds over all rounds. For other HFRs, the percentage of successful laboratories varied from 44 to 100%. The evaluation of TBBPA, DBDPE, and 2,4,6-TBP was not possible because the number of participating laboratories was too small. Only seven laboratories participated in the ICI/EQUAS scheme for OPFR metabolites and five of them were successful for at least two biomarkers. Nevertheless, the evaluation of laboratory performance using Z-scores in the first three rounds required an alternative approach compared to HFRs because of the small number of participants and the high variability of experts' results. The obtained results within the ICI/EQUAS programme showed a significant core network of comparable European laboratories for HBM of BDE-47, BDE-153, BDE-209, α-HBCD, γ-HBCD, anti-DP, and syn-DP. On the other hand, the data revealed a critically low analytical capacity in Europe for HBM of TBBPA, DBDPE, and 2,4,6-TBP as well as for the OPFR biomarkers.
CRIS-Team Scopus Importer:2021-08-06
Keywords: External quality assurance scheme (EQUAS); Halogenated flame retardants (HFRs); HBM4EU; Human biomonitoring (HBM); Interlaboratory comparison investigation (ICI); Organophosphorus flame retardants (OPFRs)